Deepening Fornix Technique Using Central Split-Medium Thickness Skin Graft to Treat Contracted Anophthalmic Sockets - AlHassan, Sultan; Galindo-Ferreiro, Alicia; Khandekar, Rajiv [UNESP]; AlShaikh, Osama [UNESP]; Schellini, Silvana Artioli [UNESP] (Lippincott Williams & Wilkins, 2018)
Purpose: The aim of thhis study was to present the outcomes of postauricular split-medium thickness skin graft (SMTSG) to treat anophthalmic sockets with contracted fornices. Methods: This case series enrolled patients with grade 2 or 3 anophthalmic sockets between 2015 and 2016. Data were collected on patient demographics, objective and subjective parameters preoperatively and 180 days postoperatively. Success of the surgery was graded on the height of the graft, the depth of the superior and inferior fornices, and presence/abscence of lagophthalmos, entropion, and ability to retain an external prosthesis. Results: Eighteen patients were enrolled with a mean age of 35.91 +/- 18 years. The median height of the graft was 22 rum (25% quartile = 18.75) when removed and 20 nun (25% quartile = 16) postoperatively. The median depth of the superior fornix was 6.5 mm (25% quartile = 4.5 mm) preoperatively and 10 mm (25% quartile = 8 mm) postoperatively (P = 0.5). The median inferior fornix depth was 7 mm (25% quartile = 3.5 mm) preoperatively and 8 nun (25% quartile = 5 mm) (P = 0.27) postoperatively. Preoperatively, there were 13 (72.2%) patients with lagophthalmos, 10 (44.4%) with entropion, 3 (37.5%) with poor prosthesis retention, and 5 (62.5%) who were unable to retain the prosthesis. Postoperatively, 7 (38.9%) patients had lagophthamos, 1 (5.6%) had entropion, and all the patients could retain the prosthesis. None of the sockets had a foul odor postoperatively. Conclusions: Postauricular SMTSG achieves successful outcomes for the treatment of contracted anophthalmic sockets, reshaping the anterior socket surface and deepening the fornices.
Keywords: Contracted socket; fornix deepening; postauricular graft; split medium thickness skin graft